2013
DOI: 10.1586/14737167.2014.868310
|View full text |Cite
|
Sign up to set email alerts
|

A review of economic impact of targeted oral anticancer medications

Abstract: There has been a rapid increase in the use of targeted oral anticancer medications (OAMs) in the past decade. As OAMs are often expensive, economic consideration play a significant role in the decision to prescribe, receive or cover them. This paper performs a systematic review of costs or budgetary impact of targeted OAMs to better understand their economic impact on the healthcare system, patients as well as payers. We present our review in a summary table that describes the method and main findings, take in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…However, the recent introduction of oral anticancer treatments (OATs) has led to a shift in the management of patients suffering from cancer from outpatient settings to home-administered treatments 1 . This trend is expected to continue, since it was estimated that in 2008, 25%-30% of molecules under development in oncology were designed for oral administration and 40% of OATs have been approved within the last 7 years 1,2 . In addition, the majority of patients suffering from advanced cancers prefer OATs to IV treatments as long as similar efficacy can be guaranteed 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the recent introduction of oral anticancer treatments (OATs) has led to a shift in the management of patients suffering from cancer from outpatient settings to home-administered treatments 1 . This trend is expected to continue, since it was estimated that in 2008, 25%-30% of molecules under development in oncology were designed for oral administration and 40% of OATs have been approved within the last 7 years 1,2 . In addition, the majority of patients suffering from advanced cancers prefer OATs to IV treatments as long as similar efficacy can be guaranteed 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The oral route is perceived as more convenient than the IV route because it reduces the impact of treatment on daily life activities and avoids outpatient clinical visits for infusions 5,6 . Nevertheless, serious concerns have been raised relating to the use of OATs and the change in cancer treatment paradigm 1 . In particular, this novel approach to drug delivery shifts the responsibility of treatment administration from healthcare providers to the patient 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the availability of patient‐level data, we preferred this approach to avoid assumptions needed in modeling. We searched PubMed in January 2014 using the following keywords, as modified from our previous studies, to realize which cost issue(s) of SCLC had been reported in the literature: ([small cell lung cancer] NOT [non‐small cell lung]) AND ([“costs and cost analysis”{MeSH}] OR costs[Title/Abstract] OR cost effective*[Title/Abstract]) OR (cost*[Title/Abstract] OR “costs and cost analysis”[MeSH:noexp] OR cost benefit analysis*[Title/Abstract] OR cost‐benefit analysis[MeSH] OR health care costs MeSH: noexp) . We found that various issues, including work‐up modality, chemotherapy intensity, prophylactic cranial irradiation, granulocyte colony‐stimulating factor, prophylactic antibiotics, second line treatment, new drugs, and overall cost, had been reported since 2000 .…”
Section: Discussionmentioning
confidence: 99%
“…Phase I identified immunotherapy agents that have already been discussed in systematic reviews published after January 1, 2012, so as to restrict to recently published systematic reviews. We used balanced search filters for costs or economics in the PubMed (("costs and cost analysis" [ [57][58][59] and "cancer" and the above drug list in Pubmed 60 and limited to systematic reviews published after January 1, 2012. After excluding the subset of the drugs identified from phase I (decided by consensus between two authors (Chien & Shih)), we then proceeded to phase II in which we performed a comprehensive literature search using the remaining drugs on the master list (the modified list) AND the above search filters for costs or economics AND cancer in Pubmed on Feb 6th, 2014.…”
Section: Methodsmentioning
confidence: 99%